VERTIGO IN INTERNAL MEDICINE PRACTICE - O. M. Drapkina; S. O. Chaparkina (Столичная издательская компания, 2015)
Vertigo is observed in 30% of people above 65 y.o. and in 50% of peoples above 80 y.o. This disorder significantly affects patient quality of life and can be a reason of incidences, trauma and even disability. Vertigo is classified as systemic or non-systemic. It can be consequence of different disturbances. Physician of any clinical specialty can face with this problem. Identification of the vertigo cause is a quite difficult problem, but success of treatment depends on it. First of all treatment strategy should be directed to elimination of the vertigo cause.